Performance Analysis of Solar Still by Using Octagonal-Pyramid Shape in the Solar Desalination Techniques - Bipin Kumar Singh; C. Ramji; P. Ganeshan; V. Mohanavel; T. Balasundaram; V. Vignesh Kumar; B. Balasubramanian; P. Ramshankar; Adireddy Ramesh; Subash Thanappan (International Journal of Photoenergy)
This research work explored and compared the experimental performance of a solar still having novel octagonal-pyramid shape with a single slope solar still. It is found that the novel still provides twice distillation compared with conventional still. The experiments also evaluated the desalination productivity of octagonal-pyramid solar still by varying the depth of saline water inside the basin and angle of inclination of glass cover. It is observed that the optimum condition for high distillation is obtained when depth of water inside the basin is 5 cm with angle of inclination of glass cover which is 30°. Four types of water, i.e., underground borewell water, sea water, leather industry effluent, and plastic industry effluent were also used to see the effect on distillation. Results showed that underground borewell water provides high distillation due to low density. Furthermore, the performance of the octagonal-pyramid solar still is enhanced by adding different latent heat and sensible heat materials in the octagonal-pyramid solar still. Hence, the addition of brick to the octagonal-pyramid still yields the highest productivity compared to incorporation of paraffin wax. Hence, it can be concluded that the octagonal design of the solar still has shown an increased productivity when compared to a single slope solar still (conventional still) under all the conditions.